JILBAB POLWAN PERSPEKTIF MASHOOD A. BADERIN - Saâ€™dan, Masthuriyah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2014)
The case of the veiling of policewomen shook the country last year. Former President Susilo Bambang Yudoyono wasÂ asked to take part in deciding whether policewoman should be allowed to wear the veil when on duty. Kapolri (Chief of Police in Indonesia) made the decision â€œto allowâ€ policewomen to wear the veil but then revoked the decision after a few days. Of course, there was strong argument. On the one hand, the veil is an obligationÂ for Islamic policewoman, and it is also a basic right to use the veil or not. However, the problem arises when basic rights are not accommodated by Kapolri.Â Mashood A. Baderin offers the doctrine of a â€˜margin of appreciationâ€™ in relation to the case of policewomen and the veil in Indonesia. Baderin emphasizes legal dialogue between Islamic law and International Law on Human Rights so that this dialogue between citizens, policewomen and Kapolri can lead from parochialism, violence, and rivalry towards the integrity of law in Indonesia.